2013
DOI: 10.1080/10640266.2013.779183
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Adolescents With Eating Disorders Exposed to Selective Serotonin Reuptake Inhibitors

Abstract: Retrospective chart review was used to collect data from adolescents seen in a specialized eating disorder program over an 11-year period in order to investigate any association between exposure to selective serotonin reuptake inhibitors (SSRIs) and bone mineral density (BMD). SSRI users were matched with controls based on age (within 1.5 years), gender, eating disorder diagnosis, and percent ideal body weight (within 5%), resulting in a sample of 31 pairs. SSRI users had significantly lower BMD z-scores, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Adult investigations 79 and studies of AN 10,11 have shown similar skeletal effects of antidepressants. We found that trabecular vBMD, cortical CSA, cortical thickness, section modulus, and maximal muscle CSA by pQCT were negatively correlated with antidepressant use.…”
Section: Discussionmentioning
confidence: 85%
“…Adult investigations 79 and studies of AN 10,11 have shown similar skeletal effects of antidepressants. We found that trabecular vBMD, cortical CSA, cortical thickness, section modulus, and maximal muscle CSA by pQCT were negatively correlated with antidepressant use.…”
Section: Discussionmentioning
confidence: 85%
“…Then, 14 manuscripts of the remaining 32 papers were excluded because they did not fulfill the criteria for inclusion, while the remaining 18 were included in the qualitative analysis and 5 in the quantitative analysis (Figure 1). 14,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]…”
Section: Resultsmentioning
confidence: 99%
“…Além do quadro de AN e baixo peso em si, o uso abusivo de álcool, tabagismo (MUNN-CHERNOFF et al, 2021), excesso de vitamina A (MIRA et al, 1989), baixa ingestão de cálcio, insuficiência de vitamina D (HOTTA, 2018), amenorreia , depressão e uso de medicamentos, como ISRS (COUTURIER et al, 2013), acentuam ainda mais o risco para osteoporose em indivíduos com TA.…”
Section: Osteoporoseunclassified